Doula engagement and maternal opioid use disorder (OUD): Experiences of women in OUD recovery during the perinatal period. (March 2022) - Gannon, Meghan; Short, Vanessa; Becker, Mariel; Parikh, Saloni; McGuigan, Kelly; Hand, Dennis; Keith, Scott; Abatemarco, Diane
Highlights: Women in Opioid Use Disorder (OUD) treatment who significant childhood traumaas measured by the Adverse Childhood Experiences Tool (ACE) ( M  = 5.61, SD=2.93). Women in OUD treatment perceived doulas as a positive support person during the perinatal period. Doulas served as health advocates, improving maternal perceptions of increased health literacy and self-advocacy in maternal health. Doula's emotional support and non-judgmental attitude towards women in OUD treatment facilitated perceptions of increased recovery support. Abstract: Background: Pregnant women who have substance use disorders (SUDs) are at increased risk of preterm birth, fetal mortality, and inadequate prenatal care and have higher rates of childhood trauma than their counterparts without SUDs. Doulas have been utilized with other vulnerable populations who experience trauma to increase perinatal healthcare utilization, provide emotional support, and improve birth outcomes. The objective of the current study was to examine, in women with opioid use disorder (OUD), perceptions of working with a doula in the perinatal period. Methods: Eligible participants were ≥ 18 years old, in OUD treatment, and were pregnant or recently delivered (child ≤ 3 months of age). Semi-structured interviews were used to collect tacit data on the woman's experience working with a doula during the perinatal period. All one-hour interviews were conducted over the phone and transcribed verbatim by a HIPAA compliant transcription service. Transcripts were reviewed independently by 4 coders using open coding procedures, constant comparative method of grounded theory, and inductive thematic analysis. Demographic data and history of childhood trauma information (Adverse Childhood Experiences Tool) were collected with a phone survey prior to the interview. Results: Participants' ( N  = 23) were 32.5 years of age (4.1 SD), with the majority Caucasian (71.4%), Non-Hispanic (71.4%) and Medicaid recipients (100%). Participants reported a mean of 5.61 (SD=2.93) adverse childhood experiences, indicating a significant trauma burden. Major themes uncovered in the interview transcripts revealed emotional and OUD recovery support provided by the doula and increased maternal health literacy and self-advocacy. The presence of a doula during labor/delivery reduced maternal perceptions of stigma they perceived from their healthcare providers. Conclusion: Doula engagement was associated with perceptions of increased emotional support, health literacy and self-advocacy in maternal health among women with OUD, which is significant given this population's trauma histories. This preliminary research has significant implications for improving the health of the mother child dyad affected by maternal OUD.